PENINGKATAN PERFORMA KARYAWAN: PERAN BUDAYA ORGANISASI DAN ROTASI KERJA - Rafli, Muhammad; Sjahruddin, Herman; Rapanna, Patta; Mochtar, Hasyim (Gapenas Publisher, 2024)
The high individual performance of the employees greatly helps the achievement of the vision, mission and goals of the institution, that individuals who work efficiently and effectively are believed to have high work ability and motivation so that these employees can produce high performance. This study aimed to test and analyze the effect of organizational culture and job rotation on employee performance at PT Bank Tabungan Negara (Persero) Tbk. Makassar Branch. The research approach used in this study is a positivism method by utilizing all employees as the population. Sample collection was carried out by utilizing total sampling so that 60 employees were obtained as respondents. The analysis technique used is multiple linear regression, using the SPSS version 27 application. The results of this study provided evidence that the better the organizational culture, that exists in the organization and the more intensively job rotation is carried out, the higher the performance produced by employees